Coordinated optimal control of wind farm active power : : doctoral thesis - Spudić, Vedrana (V. Spudić ; Fakultet elektrotehnike i računarstva, 2012)
ABSTRACT: With large penetration of wind energy in electricity grids, a requirement to control the wind farm active power arises. To fulfill the demands set in the new grid codes wind farms must have an ability to track the power reference demanded by the transmission system operator. The research in this thesis focuses on the design of an optimal wind farm controller that enables tracking of the power reference, while achieving reduction of the wind turbine structural loads. Such control design ensures more cost efficient way to produce electrical power from the wind when wind farm responds to requirements from the transmission system operator. The task of the wind farm controller is to distribute power references among the wind turbines. Due to significantly slower sampling time and restrictions on actuator manipulation the design of the wind farm controller requires different approach for structural loads reduction than that used for design of wind turbine controllers with that objective. The designed controller is based on the model predictive control methodology that relies on a process model, which is derived and experimentally tested. A hierarchical control design approach is used - the time scale separation observed in the system is utilised as a separation principle. The individual controllers with different sampling times are designed for the slow and the fast processes. To ensure scalability of the proposed controller design a novel implementation approach of the wind farm controller is proposed, which is based on the decomposition and parametrisation of the overall problems. The local problems are then solved off-line, while the optimal coordination problem is solved on-line, at every sampling instant. Two procedures are developed that enable efficient implementation of on-line optimisation, both of which largely outperform the classical computation approach. The proposed controller design demonstrates excellent wind farm power tracking ability with significant reduction in wind turbine loads. Using the developed computation approach, the controller is applicable for implementation on very large wind farms with hundreds wind turbines that are being built today. -